Myelin insults differentials on MRI in children: In the light of an ADEM case - Amine Naggar; Khadija Laasri; Badr Kabila; Zineb Izi; Nazik Allali; Siham El Haddad; Latifa Chat (Radiology Case Reports, 2024)
Acute disseminated encephalomyelitis (ADEM) is an acute and rapidly progressive auto-immune demyelinating disorder in the central nervous system. It is a rare disease but is more frequently observed in the pediatric population. We report a case of a monophasic postvaccination ADEM, which presented with paraparesis associated with fever. It showed a favorable evolution under corticosteroids, without recurrence after 3 years of follow-up. The diagnosis was established due to the postvaccination context and the MRI abnormalities characteristics. This case prompted a general discussion about the etiologies of myelin insults in children, especially demyelinating disorders, by shedding the light on their MRI features.